Shatterzone of empires : coexistence and violence in the German, Habsburg, Russian, and Ottoman borderlands - Barṭov, ʾOmer 1954- HerausgeberIn; Weitz, Eric D. 1953- HerausgeberIn (Indiana University Press, 2013)
Introduction : coexistence and violence in the German, Habsburg, Russian, and Ottoman borderlands / Omer Bartov and Eric D. Weitz -- The traveler's view of Central Europe : gradual transitions and degrees of difference in European borderlands / Larry Wolff -- Megalomania and angst : the nineteenth-century mythicization of Germany's eastern borderlands / Gregor Thum -- Between empire and nation state : an outline for a European contemporary history of the Jews, 1750-1950 / Dan Diner -- Jews and others in vilna-Wino-Vilnius : invisible neighbors, 1831-1948 / Theodore R. Weeks -- Our laws, our taxes, and our administration : citizenship in imperial Austria / Gary B. Cohen -- Marking national space on the Habsburg Austrian borderlands, 1880-1918 / Pieter M. Judson -- Travel, railroads, and identity formation in the Russian empire / Frithjof Benjamin Schenk -- Germany and the Ottoman borderlands : the entwining of imperial aspirations, revolution, and ethnic violence / Eric D. Weitz -- The central state in the borderlands : Ottoman eastern Anatolia in the late nineteenth century / Elke Hartmann -- Borderland encounters in the Carpathian Mountains and their impact on identity formation / Patrice M. Dabrowski -- Mapping the hungarian borderlands / Robert Nemes -- A strange case of antisemitism : Ivan Franko and the Jewish issue / Yaroslav Hrytsak -- Nation state, ethnic conflict, and refugees in Lithuania, 1939-1940 / Tomas Balkelis -- The Young Turks and the plans for the ethnic homogenization of Anatolia / Taner Akçam